Increased DHEAS and Decreased Total Testosterone Serum Levels in a Subset of Men with Early-Onset Androgenetic Alopecia: Does a Male PCOS-Equivalent Exist? - Rossella Cannarella; Rosita A. Condorelli; Federica Dall’Oglio; Sandro La Vignera; Laura M. Mongioì; Giuseppe Micali; Aldo E. Calogero (International Journal of Endocrinology)
Background. Increased dehydroepiandrosterone sulfate (DHEAS) levels have been reported in men with early-onset (<35 years) androgenetic alopecia (AGA). It has been suggested that a male polycystic ovarian syndrome- (PCOS-) equivalent, defined as an endocrine syndrome with a metabolic background and a PCOS-like hormonal pattern, predisposing to type II diabetes mellitus (DM II), cardiovascular and prostate diseases later in life, may occur in at least a part of these men. The gonadal function, including sperm parameters and total testosterone (TT) levels, has been investigated in a low number of these men. Objective. The aim of the study was to assess gonadal and adrenal function in a subset of men with early-onset AGA and controls. Methods. 43 men with early-onset AGA and 36 controls were screened for DHEAS, TT, glycaemia, insulin, gonadotropins, 17α-hydroxyprogesterone (17αOH-P), testicular volume (TV), fat mass percentage, and sperm conventional parameters. Among men with AGA, we identified Group 1 (n = 21), as those with at least one of the following parameters: body mass index (BMI) >25 kg/m2, insulin resistance (IR), and/or SHBG <25 nmol/l. Results. Patients with early-onset AGA had higher mean (±SD) BMI (25.5 ± 3.8 vs. 23.7 ± 3.0 kg/m2; P<0.05) and 17αOH-progesterone (2.1 ± 0.9 vs. 1.5 ± 0.6 ng/ml; P<0.05) compared to controls. Group 1 had higher BMI (27.9 ± 3.8 vs. 23.7 ± 3.8 ml; P<0.05), fat-mass percentage (17.5 ± 4.1 vs. 13.2 ± 5.3; P<0.05), HOMA index (2.5 ± 1.8 vs. 1.5 ± 0.7; P<0.05), DHEAS (323.3 ± 112.6 vs. 257.8 ± 107.1 μg/dl; P<0.05), seminal fluid volume (4.2 ± 2.8 vs. 2.8 ± 1.3 ml; P<0.05), lower TT (5.16 ± 1.70 vs. 6.47 ± 4.30 ng/ml; P=0.016), and left TV (12.3 ± 2.8 vs. 15.0 ± 4.3 ml; P<0.05) compared to controls. Conclusion. Men with early-onset AGA and at least one among BMI >25 kg/m2, IR, and SHBG <25 nmol/l have increased DHEAS levels and a worse gonadal steroidogenesis. They might have a greater risk to develop gonadal dysfunction later in life. These criteria may be used to define male PCOS-equivalent.